DESAIN MONITOR DAN KONTROL JARAK JAUH PROTOTIPE RUANG CERDAS MENGGUNAKAN PAPAN INTEL GALILEO SEBAGAI IMPLEMENTASI INTERNET OF THINGS - Eridani, Dania (Jurnal Sistem Komputer, 2017)
The proper way of using room facility often neglected by its user. Human negligence is the main factor of this problem. Internet of Things (IoT) is one of automation technology that used Internet as the control mechanism. This research consist of monitoring and control design of the smart room that able to control the door and the lamp of the room in short and long distance so that the facilities is used efficiently. The design built is the control design for smart room consists of TMP36 as temperature sensor, touch sensor, solenoid door lock, keypad, BH1750FVI as ambient light sensor, lamp, LED as an indicator, Intel Galileo board and Blynk application. Control mechanism can be done directly to the prototype or in a long distance by using smartphone. The result shows that the smart room control design can be implemented well.